Endoscopically Assisted Transumbilical Single-Incision Laparoscopic Gastric Resection for GIST Treatment. (3rd March 2016) - Pitiakoudis, Michail; Zezos, Petros; Kouklakis, Georgios; Tsalikidis, Christos; Romanidis, Konstantinos; Vradelis, Stergios; Tsaroucha, Alexandra K.; Kakolyris, Stylianos; Simopoulos, Constantinos
ABSTRACT: Purpose: Complete surgical resection with negative margins without lymphadenectomy is the treatment of choice for nonmetastatic Gastrointestinal Stromal Tumors (GISTs). Laparoscopic resection of gastric GISTs <5 cm is an acceptable and oncologically feasible, safe, and effective treatment. We present our experience of an endoscopically assisted minimally invasive transumbilical single-incision laparoscopic (SILS) technique for gastric GISTs resection. Methods: Four patients with small gastric GISTs ≤5 cm located on the greater curvature or the anterior wall were resected with SILS by using a lesion-lifting technique under the guidance of flexible gastroscopy. Results: The technique was feasible and safe and offered significant advantages in locating the tumor and controlling the resection margins. There were no major intraoperative or postoperative complications, conversions, or tumor ruptures. Pathology showed low-risk GISTs resected with disease-free margins without tumor rupture. No recurrences have been observed. Conclusion: The endoscopically assisted SILS wedge gastrectomy is a feasible, safe, and advantageous technique for the treatment of the greater curvature or anterior wall gastric GISTs.